ISOLASI BAKTERI PLANT GROWTH PROMOTING RHIZOBAKTERIA (PGPR) LOKAL DARI ENDOFIT AKAR TANAMAN KELAPA SAWITDAN UJI ANTAGONIS TERHADAP PENYAKIT JAMUR AKAR PUTIH - Hilwa Walida (JURNAL AGROPLASMA, 2014)
White root fungus disease has become the most damaging root disease in rubber trees in both Africa and Asia that supplies 98% of rubber products to the world market. Chemical control by using pesticide was a common root control of white root fungus. PGPR (Plant Growth Promoting Rhizobacteria) could be one of the solutions in biological control of environmentally to against white root fungi. The aims of yhis study were to obtain isolates of local PGPR bacteria from the root endophytes of oil palm trees, to know the morphological characteristics of local PGPR isolates from root endophytes of oil palm plants, and to know the potential of biological control agents againts white root fungus disease. This research was conducted by using descriptive analysis method. The results showed that there were 9 bacterial isolates from the root endophytes of oil palm plants with different macroscopic morphological characteristic and there were 9 isolatesable to inhibite the growth of white root fungus with the biggest potential was A5 isolate. Keywords : PGPR, Root Endophytes of Palm Oil Plant, Rigidoporus microporus